Intelligent SEI film, preparation method thereof and application of intelligent SEI film in lithium battery

Carbon nanotubes are generated through focused ion beam etching and chemical vapor deposition reactions, and intelligent SEI films are prepared in combination with electrospinning process, which solves the problem of cycle life and performance degradation of lithium batteries caused by volume deformation of metal lithium negative electrodes, and achieves higher cycle stability and discharge capacity.

CN119686032APending Publication Date: 2025-03-25PINGGAO GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510019396.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The metal lithium negative electrode has a cycle life and performance degraded due to volume deformation in lithium-ion batteries. The prior art requires strict magnetic field strength and electrolyte composition in the preparation of SEI films, resulting in unstable performance.

Method used

Focused ion beam etching technology is used to cut nanoparticles from the surface of shape memory alloys, and carbon nanotubes are generated through chemical vapor deposition reactions, and intelligent SEI films are prepared in combination with electrospinning process.

Benefits of technology

The prepared smart SEI film has excellent electrochemical and mechanical properties, which can effectively suppress the volume expansion of the metal lithium negative electrode and improve the cycle stability and discharge capacity of the lithium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119686032A_ABST
    Figure CN119686032A_ABST
Patent Text Reader

Abstract

The invention relates to an intelligent SEI film, a preparation method thereof and application of the intelligent SEI film in a lithium battery, and the preparation method comprises the following steps: S1, cutting the surface of a shape memory alloy by using a focused ion beam etching technology to obtain shape memory alloy nanoparticles; s2, by taking ethanol as a carbon source and the shape memory alloy nanoparticles as a catalyst, carrying out chemical vapor deposition reaction under the protection of inert gas to obtain carbon nanotubes; s3, dissolving the shape memory alloy nanoparticle catalyst, carbon nanotubes, lithium fluoride and lithium carbonate in the mixed solution to obtain an electrostatic spinning precursor solution; and S4, performing an electrostatic spinning process on the electrostatic spinning precursor solution to obtain a fiber membrane, namely the intelligent SEI membrane. The prepared intelligent SEI film has excellent electrochemical performance and mechanical performance, and can effectively inhibit volume expansion of a metal lithium negative electrode in a long-acting cycle process, so that the cycle stability and the discharge capacity of a lithium battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to an intelligent SEI film and a preparation method thereof and application in lithium batteries. Background Art

[0002] With the rapid development of new energy technologies, lithium-ion batteries, as efficient and environmentally friendly energy storage devices, have been widely used in electric vehicles, portable electronic devices and other fields. In lithium-ion batteries, the performance of the negative electrode material directly determines the overall performance of the battery. Metallic lithium is regarded as the most promising negative electrode material in the next generation of lithium-ion batteries due to its extremely high theoretical specific capacity (3860mAh / g). However, metallic lithium anodes face a series of challenges in practical applications, the most prominent of which is the problem of volume deformation during long-term cycling.

[0003] During the charge and discharge process, the volume of the metal lithium negative electrode changes significantly due to the insertion and extraction of lithium ions. This volume deformation not only causes the fragmentation and shedding of the metal lithium, but also forms electronically insulating "dead lithium", which seriously affects the cycle life and performance of the lithium battery. Therefore, how to effectively inhibit the volume deformation of the metal lithium negative electrode and improve the cycle stability and life of the lithium battery has become a key issue that needs to be solved in the current lithium-ion battery research field.

[0004] To solve the above problems, researchers have proposed a series of strategies, among which constructing a stable solid electrolyte interface (SEI) film is considered to be an effective method. In the prior art, patent CN111477967B discloses a method for preparing SEI film by magnetization, and the preparation method includes the following preparation steps: 1) assembling cathode sheet, anode sheet and isolation membrane into a bare battery cell, injecting electrolyte into the outer shell of the bare battery cell, and standing until the cathode sheet and anode sheet are fully infiltrated to obtain a prefabricated battery cell; 2) placing the prefabricated battery cell in a forming machine for formation, applying a magnetic field to the prefabricated battery cell during formation, and performing formation treatment under the action of the magnetic field. After the formation treatment, an SEI film is formed on the surface of the anode sheet. This method improves the charge and discharge efficiency, cycle performance and rate performance to a certain extent. However, this method requires applying a magnetic field to the prefabricated battery cell during the formation process. Improper control of the magnetic field strength or instability will make the SEI film performance extremely unstable. At the same time, the composition, concentration and properties of the electrolyte have an important influence on the composition, structure and performance of the SEI film. If the composition or properties of the electrolyte are not suitable, it will also lead to unstable formation of the SEI film and poor performance. Therefore, it is necessary to develop a more efficient and stable method to actively suppress the volume deformation of the metal lithium negative electrode and improve the cycle life and performance of the lithium battery. Summary of the invention

[0005] The purpose of the present invention is to provide an intelligent SEI film and a preparation method thereof and application in lithium batteries to solve the technical problems of volume deformation of the metal lithium negative electrode in the prior art lithium-ion battery and reduced cycle life and performance of the lithium battery.

[0006] To achieve the purpose of the present invention, the specific technical solutions provided by the present invention are as follows: A first aspect of the present invention provides a method for preparing a smart SEI film, comprising the following steps: S1. Using focused ion beam etching technology, cutting is performed from the surface of the shape memory alloy to obtain shape memory alloy nanoparticles of 20-50 nm; S2, using ethanol as a carbon source and the shape memory alloy nanoparticles obtained in step S1 as a catalyst, and obtaining carbon nanotubes through chemical vapor deposition reaction under the protection of an inert gas; S3, mixing ethanol and deionized water to obtain a mixed solution, and then dissolving shape memory alloy nanoparticles, carbon nanotubes, lithium fluoride and lithium carbonate in the mixed solution to obtain an electrospinning precursor solution; S4. The electrospinning precursor solution is subjected to an electrospinning process and pressed to obtain a fiber membrane with a thickness of 20 to 100 μm, which is the smart SEI membrane.

[0007] Preferably, in step S1, the conditions for focused ion beam etching are: using 30 kV high voltage gallium ions as the ion source, controlling the ion beam current to 600-800 pA, and etching time to 1-3 minutes.

[0008] Preferably, the shape memory alloy is a shape memory alloy having a transformation temperature of -20 to 100°C.

[0009] More preferably, the shape memory alloy includes one or both of nickel-titanium shape memory alloy and copper-zinc shape memory alloy.

[0010] Preferably, in step S2, the chemical vapor deposition reaction is carried out at 600-800°C for 30-50 minutes, and the mass ratio of the catalyst to ethanol is 1:(5-10).

[0011] Preferably, in step S3, the mixing volume ratio of ethanol and deionized water is (1-3): (1-3), the mass ratio of shape memory alloy nanoparticle catalyst, carbon nanotubes, lithium fluoride and lithium carbonate is (1-3): (0.3-0.8): (0.5-1.5): (0.5-1.5), and the mass percentage of carbon nanotubes in the mixed solution of ethanol and deionized water is 0.3-0.8%.

[0012] Preferably, in step S4, the conditions of the electrospinning process are: voltage of 10-20 kV, syringe propulsion speed of 0.1 mL / h-10 mL / h, and distance from the spinning needle to the receiving plate of 18 cm-20 cm.

[0013] Preferably, in step S4, the fiber membrane obtained by the electrospinning process is pressed at a pressure of 20-30 MPa at 40-60° C. for 20-40 minutes to obtain a smart SEI membrane with a thickness of 20-50 μm.

[0014] The second aspect of the present invention also provides a smart SEI film, which is prepared by the above preparation method.

[0015] The third aspect of the present invention also provides an application of an intelligent SEI membrane in a lithium battery, wherein the intelligent SEI membrane is assembled together with a metal lithium negative electrode, a sulfur positive electrode and a polypropylene separator into a lithium-sulfur battery, and an electrolyte is dripped into it; or the intelligent SEI membrane is assembled together with a metal lithium negative electrode, a lithium iron phosphate positive electrode and a polypropylene separator into a metal lithium battery, and an electrolyte is dripped into it.

[0016] The smart SEI film of the present invention, its preparation method and application in lithium batteries have the following beneficial effects: 1. The smart SEI film prepared by the present invention has excellent electrochemical and mechanical properties. It utilizes the reversible volume deformation advantage of the shape memory material during phase transition to resist and inhibit the volume expansion of the metal lithium negative electrode during long-term cycling, thereby improving the cycle stability and discharge capacity of the lithium battery.

[0017] 2. Compared with traditional film-forming technology, the SEI membrane prepared by the electrospinning process adopted in the present invention has the advantages of large specific surface area, high porosity, and controllable pore size. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a transmission electron microscope image of carbon nanotubes in an embodiment of the present invention; Figure 2 The lithium-sulfur battery cycle performance curves of Example 1 and Comparative Example 1 of the present invention; Figure 3 The metal lithium battery cycle performance curves of Example 2 and Comparative Example 2 of the present invention; Figure 4 The graphs are the cycle performance curves of the lithium-sulfur batteries of Example 3 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0019] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation method, structure, characteristics and effects of the present invention are described in detail below in combination with the preferred embodiments.

[0020] Example 1 This embodiment provides a smart SEI film and a method for preparing the same, the method comprising the following specific steps: S1. Nickel-titanium shape memory alloy nanoparticles with a diameter of 30 nm were obtained by cutting the surface of nickel-titanium shape memory alloy with a shape memory transition temperature of 10°C using focused ion beam etching technology.

[0021] The conditions for focused ion beam etching are: using a 30 kV gallium ion source, controlling the ion beam current to 600 pA, and etching time to 2 minutes.

[0022] S2, using the nickel-titanium shape memory alloy nanoparticles obtained in step S1 as a catalyst, using ethanol as a carbon source, reacting in an argon atmosphere at a high temperature of 800°C for 40 minutes to obtain a controllably synthesized carbon nanotube network, wherein the mass ratio of the catalyst to the ethanol is 1:5. Figure 1 The transmission electron microscope image of carbon nanotubes is shown. Figure 1 It can be seen that carbon nanotubes were grown and synthesized using nickel-titanium nanoparticles as catalysts.

[0023] S3. Mix ethanol and deionized water in a volume ratio of 1:1 to obtain a mixed solution, and then dissolve nickel-titanium shape memory alloy nanoparticles, carbon nanotubes, lithium fluoride and lithium carbonate in the mixed solution, wherein their mass percentages in the mixed solution are: 2.0% nickel-titanium shape memory alloy nanoparticle catalyst, 0.5% carbon nanotubes, 1.0% lithium fluoride, 1.0% lithium carbonate, and mix well to obtain an electrospinning precursor solution.

[0024] S4, electrospinning the electrospinning precursor solution, pressing at 50°C and 25MPa for 30 minutes, to obtain a smart SEI membrane with a thickness of 50μm. The electrospinning process conditions are: voltage of 10 kV, syringe propulsion speed of 1mL / h, and the distance from the spinning needle to the receiving plate of 18 cm.

[0025] Example 2 S1. Nickel-titanium shape memory alloy nanoparticles with a diameter of 20 nm were obtained by cutting the surface of nickel-titanium shape memory alloy with a shape memory transition temperature of 50°C using focused ion beam etching technology.

[0026] The conditions for focused ion beam etching are: using a 30 kV gallium ion source, controlling the ion beam current to 800 pA, and etching time to 3 minutes.

[0027] S2, using the nickel-titanium shape memory alloy nanoparticles obtained in step S1 as a catalyst, using ethanol as a carbon source, reacting at a high temperature of 600° C. for 40 minutes under an argon protective atmosphere to obtain controllably synthesized carbon nanotubes. The mass ratio of the catalyst to the ethanol is 1:8.

[0028] S3. Mix ethanol and deionized water in a volume ratio of 1:1 to obtain a mixed solution, and then dissolve nickel-titanium shape memory alloy nanoparticles, carbon nanotubes, lithium fluoride and lithium carbonate in the mixed solution, wherein their mass percentages in the mixed solution are: 2.0% nickel-titanium shape memory alloy nanoparticle catalyst, 0.5% carbon nanotubes, 1.0% lithium fluoride, 1.0% lithium carbonate, and mix well to obtain an electrospinning precursor solution.

[0029] S4, electrospinning the electrospinning precursor solution, pressing at 50°C and 25MPa for 30 minutes, to obtain a smart SEI membrane with a thickness of 60μm. The electrospinning process conditions are: voltage of 20 kV, syringe propulsion speed of 0.5 mL / h, and the distance from the spinning needle to the receiving plate of 20 cm.

[0030] Example 3

[0031] S1. Nickel-titanium shape memory alloy nanoparticles with a diameter of 30 nm were obtained by cutting the surface of a copper-zinc shape memory alloy with a shape memory transition temperature of -10°C using focused ion beam etching technology.

[0032] The conditions for focused ion beam etching are: using a 30 kV gallium ion source, controlling the ion beam current to 800 pA, and etching time to 3 minutes.

[0033] S2. Using the copper-zinc shape memory alloy nanoparticles obtained in step S1 as a catalyst and ethanol as a carbon source, reacting at a high temperature of 800° C. for 40 minutes under an argon protective atmosphere to obtain controllably synthesized carbon nanotubes. The mass ratio of the catalyst to the ethanol is 1:6.

[0034] S3. Mix ethanol and deionized water in a volume ratio of 1:1 to obtain a mixed solution, and then dissolve copper-zinc shape memory alloy nanoparticles, carbon nanotubes, lithium fluoride and lithium carbonate in the mixed solution, wherein their mass percentages in the mixed solution are: nickel-titanium shape memory alloy nanoparticle catalyst 2.0%, carbon nanotubes 0.5%, lithium fluoride 1.0%, lithium carbonate 1.0%, and mix well to obtain an electrospinning precursor solution.

[0035] S4, electrospinning the electrospinning precursor solution, pressing at 50°C and 25 MPa for 30 minutes, to obtain a smart SEI membrane with a thickness of 20 μm. The electrospinning process conditions are: voltage of 15 kV, syringe propulsion speed of 1 mL / h, and the distance from the spinning needle to the receiving plate of 20 cm.

[0036] Application Example 1 With elemental sulfur as the positive electrode, metallic lithium as the negative electrode, and polypropylene as the separator, the smart SEI film with a thickness of 50 μm prepared in Example 1 is assembled into a lithium-sulfur battery together with the metallic lithium negative electrode, the sulfur positive electrode and the polypropylene separator, and the electrolyte is dripped into it.

[0037] The charge and discharge performance of the lithium-sulfur battery was tested using a Blue Electric battery tester in the temperature range of 0°C to 20°C. After 100 cycles, the discharge capacity of the lithium-sulfur battery with an intelligent SEI film was 880 mAh / g.

[0038] Application Example 2 With lithium iron phosphate as the positive electrode, metallic lithium as the negative electrode, and polypropylene as the separator, the smart SEI membrane with a thickness of 60 μm prepared in Example 2 is assembled into a metal lithium battery together with the metallic lithium negative electrode, lithium iron phosphate positive electrode and polypropylene separator, and the electrolyte is dripped into it.

[0039] The charge and discharge performance of the metal lithium battery was tested using a Blue Electric battery tester in the temperature range of 40°C to 60°C. After 250 cycles, the discharge capacity of the metal lithium battery with an intelligent SEI film was 150 mAh / g.

[0040] Application Example 3 With elemental sulfur as the positive electrode, metallic lithium as the negative electrode, and polypropylene as the separator, the smart SEI membrane with a thickness of 20 μm prepared in Example 3 is assembled into a lithium-sulfur battery together with the metallic lithium negative electrode, the sulfur positive electrode and the polypropylene separator, and the electrolyte is dripped into it.

[0041] The charge and discharge performance of the lithium-sulfur battery was tested using a Blue Electric battery tester in the temperature range of -20°C to 0°C. After 250 cycles, the discharge capacity of the lithium-sulfur battery with an intelligent SEI film was 901 mAh / g.

[0042] Comparative Example 1 Compared with Application Example 1, a lithium-sulfur battery was assembled with elemental sulfur as the positive electrode, metallic lithium as the negative electrode, and polypropylene as the separator, and the electrolyte was dripped in. The charge and discharge performance of the lithium-sulfur battery was tested in the temperature range of 0°C to 20°C using a blue battery tester. After 100 cycles, the discharge capacity of the lithium-sulfur battery was 650 mAh / g. The results are as follows: Figure 2 shown.

[0043] Comparative Example 2 Compared with Application Example 2, lithium iron phosphate is used as the positive electrode, metal lithium is used as the negative electrode, and polypropylene is used as the separator to assemble a metal lithium battery, and the electrolyte is dripped in. The charge and discharge performance of the metal lithium battery is tested in the temperature range of 40℃ to 60℃ using a blue battery tester. After 250 cycles, the discharge capacity of the metal lithium battery is 121 mAh / g. The results are as follows Figure 3 shown.

[0044] Comparative Example 3 Compared with Application Example 3, a lithium-sulfur battery was assembled with elemental sulfur as the positive electrode, metallic lithium as the negative electrode, and polypropylene as the separator, and the electrolyte was dripped in. The charge and discharge performance of the lithium-sulfur battery was tested in the temperature range of -20℃ to 0℃ using a blue battery tester. After 250 cycles, the discharge capacity of the lithium-sulfur battery was 587 mAh / g. The results are as follows: Figure 4 shown.

[0045] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a smart SEI film, characterized in that: The following steps are involved: S1. Cut the surface of the shape memory alloy using focused ion beam etching technology to obtain shape memory alloy nanoparticles of 20-50 nm; S2, using ethanol as a carbon source and the shape memory alloy nanoparticles obtained in step S1 as a catalyst, and obtaining carbon nanotubes through chemical vapor deposition reaction under the protection of an inert gas; S3, mixing ethanol and deionized water to obtain a mixed solution, and then dissolving shape memory alloy nanoparticles, carbon nanotubes, lithium fluoride and lithium carbonate in the mixed solution to obtain an electrospinning precursor solution; S4. The electrospinning precursor solution is subjected to an electrospinning process and pressed to obtain a fiber membrane with a thickness of 20 to 100 μm, which is the smart SEI membrane.

2. The method for preparing a smart SEI film according to claim 1, characterized in that: In step S1, the conditions for focused ion beam etching are: using 30 kV high voltage gallium ions as the ion source, controlling the ion beam current to 600-800 pA, and etching time to 1-3 minutes.

3. The method for preparing a smart SEI film according to claim 1, characterized in that: Shape memory alloy is a shape memory alloy with a transformation temperature of -20~100℃.

4. The method for preparing a smart SEI film according to claim 1, characterized in that: In step S2, the chemical vapor deposition reaction is carried out at 600-800°C for 30-50 minutes, and the mass ratio of the catalyst to ethanol is 1:(5-10).

5. The method for preparing a smart SEI film according to claim 1, characterized in that: In step S3, the mixing volume ratio of ethanol and deionized water is (1-3): (1-3), the mass ratio of shape memory alloy nanoparticles, carbon nanotubes, lithium fluoride and lithium carbonate is (1-3): (0.3-0.8): (0.5-1.5): (0.5-1.5), and the mass percentage of carbon nanotubes in the mixed solution of ethanol and deionized water is 0.3-0.8%.

6. The method for preparing a smart SEI film according to claim 1, characterized in that: In step S4, the conditions of the electrospinning process are: the voltage is 10-20 kV, the syringe propulsion speed is 0.1 mL / h-10 mL / h, and the distance from the spinning needle to the receiving plate is 18 cm-20 cm.

7. The method for preparing a smart SEI film according to claim 1, characterized in that: In step S4, the fiber membrane obtained by the electrospinning process is pressed at 40-60°C and a pressure of 20-30 MPa for 20-40 minutes to obtain a smart SEI membrane with a thickness of 20-50 μm.

8. A smart SEI film, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.

9. The use of a smart SEI film according to claim 8, characterized in that: Smart SEI membrane is used in lithium batteries.

10. The use of a smart SEI film according to claim 9, characterized in that: The smart SEI membrane is assembled together with a metal lithium negative electrode, a sulfur positive electrode and a polypropylene separator into a lithium-sulfur battery, and an electrolyte is dripped into it; or the smart SEI membrane is assembled together with a metal lithium negative electrode, a lithium iron phosphate positive electrode and a polypropylene separator into a metal lithium battery, and an electrolyte is dripped into it.